Front Cover Picture: Ruthenium(II)‐ or Rhodium(III)‐Catalyzed Grignard‐Type Addition of Indolines and Indoles to Activated Carbonyl Compounds (Adv. Synth. Catal. 17/2016). Issue 17 (29th July 2016) - Jo, Hyeim; Park, Jihye; Choi, Miji; Sharma, Satyasheel; Jeon, Mijin; Mishra, Neeraj Kumar; Jeong, Taejoo; Han, Sangil; Kim, In Su
Abstract : The front cover image, provided by In Su Kim and co‐workers, illustrates the Ru(II)‐ or Rh(III)‐catalyzed pyrimidinyl‐directed Grignard‐type C–H additions of N‐heterocycles with activated aldehydes and ketones. Details can be found in the communication on pages 2714–2720 (H. Jo, J. Park, M. Choi, S. Sharma, M. Jeon, N. K. Mishra, T. Jeong, S. Han, I. S. Kim, Adv. Synth. Catal .2016, 358, 2714–2720; DOI:10.1002/adsc.201600297 ).